PENINGKATAN HASIL BELAJAR SISWA DALAM PEMBELAJARAN IPS DENGAN MODEL PEMBELAJARAN KOOPERATIF TIPE GROUP INVESTIGATION PADA SISWA KELAS V SD - Nengsih, Yuliani; Alwi, Elma; Mayarnimar, Mayarnimar (e-Jurnal Inovasi Pembelajaran Sekolah Dasar, 2018)
This study aims to describe the improvement of social studies learning with the investigational group learning model in SDN. 27 Koto Baru, Ranah Pesisir District. This study uses a qualitative and quantitative approach. This type of research is Classroom Action Research. The research subjects were 21 teachers, observers and students. Research procedures are planning, implementation, observation, and reflection. The results of the study are learning planning obtained the results of the first cycle an average of 78.5% and the second cycle 96%. The implementation of teacher activities in the first cycle averaged 76.63% and the second cycle was 94%, and in the activities of students the first cycle averaged 71.88% and cycle II 91%. Cycle I cognitive learning outcomes averaged 66.31, and cycle II 71.98. For affective learning outcomes in the first cycle the average is 65.55 and cycle II is 80.1. Thus it can be concluded that social studies learning using the cooperative learning model Group Investigation type increases. Keywords—Learning Outcomes, Social Studies, Group Investigation Cooperative